2016
DOI: 10.1002/tox.22271
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extracts induced the colon cancer migration via regulating epithelial mesenchymal transition and metastatic genes in human colon cancer cells

Abstract: There was considerable evidence that exposure to cigarette smoke is associated with an increased risk for colon cancer. Nevertheless, the mechanism underlying the relationship between cigarette smoking and colon cancer remains unclear. Moreover, there were only a few studies on effects of complexing substance contained in cigarette smoke on colon cancer. Thus, we further investigated whether cigarette smoke extract (CSE) affects the cell cycle, apoptosis and migration of human metastatic colon cancer cells, SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In addition, a recent meta-analysis reported random-effects HR estimates (95% CI) for all-cause mortality of 1.26 (1.15-1.37) for current smokers compared with never smokers, which indicated that smoking had detrimental effects on survival even after CRC diagnosis [36]. There is some in vitro evidence that smoking could stimulate cell metastatic ability by altering epithelial-mesenchymal transition and influence chemotherapy efficacy by inducing metabolic and epigenetic alterations [37,38]. Smoking showed a strong influence on the natural history of chronic obstructive pulmonary disease (COPD) and smoking related COPD was a significant predictor of more visit to emergency room and hospital readmission in colon cancer patients treated with adjuvant chemotherapy [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent meta-analysis reported random-effects HR estimates (95% CI) for all-cause mortality of 1.26 (1.15-1.37) for current smokers compared with never smokers, which indicated that smoking had detrimental effects on survival even after CRC diagnosis [36]. There is some in vitro evidence that smoking could stimulate cell metastatic ability by altering epithelial-mesenchymal transition and influence chemotherapy efficacy by inducing metabolic and epigenetic alterations [37,38]. Smoking showed a strong influence on the natural history of chronic obstructive pulmonary disease (COPD) and smoking related COPD was a significant predictor of more visit to emergency room and hospital readmission in colon cancer patients treated with adjuvant chemotherapy [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The pro-apoptosis capacity and potential mechanism underlying Calotropin-mediated apoptosis in NSCLC cells were also analyzed. The results demonstrated that Calotropin inhibited H358 cell growth, migration and invasion by decreasing FN and VIM, and increasing Eca expression levels ( 24 , 25 ). It was also revealed that Calotropin treatment promoted apoptosis by upregulating pro-apoptosis gene and downregulating anti-apoptosis protein expression.…”
Section: Discussionmentioning
confidence: 95%
“…TPM and CSE were prepared as described in our previous studies (9). University of Kentucky 3R4F reference cigarettes were smoked on a 30-port smoking machine (CH Technologies, Westwood, NJ, USA) at 35-mL puff volume, 2-sec puff duration and 60 sec between puffs, in conformity with ISO standard 3308.…”
Section: Methodsmentioning
confidence: 99%